Fenomenologi Alfred Schutz: Studi tentang Motif Pemakaian Peci Hitam Polos - Alen Manggola; Robeet Thadi (JOPPAS: Journal of Public Policy and Administration Silampari, 2021)
ABSTRACT The purpose of the study was to determine the phenomenology of the use of plain black caps by the Bengkulu people. This research method uses qualitative research with an interpretive tradition. The results showed that the choice of motif for wearing a plain black cap explains the influence of culture/trend and comfort as a motive for wearing a cap by the wearer, and is also a form of communication as a symbol of existence. The conclusion of the study is that the motif of wearing plain black caps has become a cultural trend of the general public. The conclusion of this study is that the motive for use provides an explanation that culture, history, beauty and comfort can defeat the presence of new creations in the same product, such as the existence of plain black caps in Bengkulu. Keywords: Alfred Schutz Phenomenology, Motif, Plain Black Cap.